Honoring donors: medical students’ reflections on cadaveric dissection - Young Gyu Kwon; Myeong Namgung; Song Hee Park; Mi Kyung Kim; Chan Woong Kim; Hyo Hyun Yoo (BMC Medical Education)
Abstract Background Cadaveric dissection is an essential practice for medical students to understand human anatomy and internalize professional attitudes toward death, such as empathy and respect for the deceased. Previous studies have focused on emotional responses such as shock, anxiety, and fear at the start of dissection practice. However, limited research exists on students’ reflective thinking and perceptions before practice. This study aims is to understand premedical students’ perceptions and attitudes before dissection by analyzing their reflective writing. Methods Text network analysis of essays written in 2022 by 136 s-year premedical students before cadaveric dissection was performed. Keywords were preprocessed to extract significant themes. Centrality analysis and topic modeling were performed to analyze students’ perceptions and attitudes. Results Centrality analysis identified “cadaveric dissection,” “donation,” and “gratitude” as major keywords, indicating the students’ deep appreciation and respect for donors. Two main topics emerged from topic modeling. The first, “gratitude and respect for donors,” included keywords such as “gratitude” and “donation.” The second, “growth and responsibility of doctors through medical study and practice,” included keywords such as “study” and “medical school.” Conclusion The participants had profound gratitude and respect for donors before cadaveric dissection, which increased their motivation to learn. Analyzing reflective writing is an effective approach to understanding students’ initial perceptions and attitudes toward cadaveric dissection; further, it can inform educational strategies that aid students in forming their professional identity.